Cannabis use among youth who vape nicotine E-cigarettes: A qualitative analysis. (1st May 2022) - Davis, Danielle R.; Bold, Krysten W.; Kong, Grace; Cavallo, Dana A.; Jackson, Asti; Krishnan-Sarin, Suchitra
Abstract: Background: Nicotine vaping and cannabis use are common among youth. Among youth who use e-cigarettes, little is known about how and why they use cannabis and patterns of cannabis and nicotine co-use. Given the popularity of both products among youth, the study aim is to utilize qualitative data to better understand cannabis use among youth who use e-cigarettes. Method: Six focus groups of high schoolers who reported past-month e-cigarette use (N = 50; 52% male) were conducted to inform e-cigarette cessation programming. We conducted secondary data analysis examining report of cannabis use during focus groups. Transcripts were examined for report of cannabis use, reasons for use, and nicotine and cannabis co-use. Results: In focus groups, cannabis was commonly discussed. Youth reported vaping cannabis, however other forms of cannabis delivery were common (e.g. blunts, joints). Themes related to reasons for simultaneous use of nicotine and cannabis were to experience stronger psychoactive effects than using either product alone and needing to use less nicotine product overall. Reasons for liking cannabis were positive psychoactive effects and stress relief. Reasons for disliking were related to health concerns. Notably, when youth reported disliking cannabis due to health concerns, a common discussion was strategies to acquire and continue cannabis use in ways that they perceived mitigated health concerns. Conclusion: Qualitative evidence identified associations between e-cigarette use and cannabis use among youth. Research and interventions targeting youth using e-cigarettes should consider how to address dual use of these products. Highlights: For youth using nicotine e-cigarettes, cannabis use is common. Youth e-cigarette users report cannabis use via multiple routes of administration. Youth use e-cigs and cannabis simultaneously for stronger psychoactive effects. Youth use cannabis knowing health risks and engage in harm reduction strategies.